Distribución de productos y colecta de residuos en una red logística mediante ruteo de ruteo de vehículos abierto con ventanas de tiempo - Gerónimo Sanes, Alan Pierre (2021)
Research carried in the context of logistics, shows that today’s cities main tain an immense commercial activity due to the demand of the population, to_x000D_ satisfy their different basic needs. The demand brings positive consequences_x000D_ because when the commercial flow increases it brings development generating_x000D_ sources of employment; However, not making timely decisions would bring ne gative consequences affecting the health of citizens, for this reason it constitutes_x000D_ a challenge for the authorities since maintaining sustainability is important._x000D_ Making the logistics network viable for an optimal supply of products and_x000D_ the pickup of generated waste, was possible through the development of a binary_x000D_ integer programming model and a metaheuristic called GRASP, based on vehicle_x000D_ routing with time windows. The results obtained with the implementations show_x000D_ the importance of the proposal, which can be extended to real situations without_x000D_ the need for major changes